Analisis Pengaruh Promosi di Media Sosial dan Word of Mouth Terhadap Keputusan Pembelian Susu Yoghurt: Studi kasus pada konsumen Family Moo Kabupaten Cianjur - Dani, Asep; Dasipah, Euis; Sukmawati, Dety (Papanda Publisher, 2024)
This study aims to analyze the effect of promotion on social media and word of mouth (WOM) on purchasing decisions for Family Moo yoghurt milk in Cianjur Regency. This study was conducted by identifying the characteristics of respondents based on gender, age, and occupation and measuring the effectiveness of social media promotions and WOM in influencing purchasing decisions. Data was collected through a survey conducted in 2023, involving respondents with various demographic backgrounds.The results showed that the majority of respondents were female (65%) with the largest age group being 20-30 years old (45%). Respondents' occupations were dominated by the category of “others,” including housewives (40%). The validity and reliability tests of the measuring instruments showed satisfactory results, with all promotion, WOM, and purchase decision items measured as valid and reliable. The integration between social media promotion and WOM is very effective in influencing consumer purchasing decisions for Family Moo yoghurt milk. Therefore, it is recommended that companies improve promotional strategies on social media with more creative and interactive content and facilitate positive WOM through loyalty